Video Game Creation as an Opportunity to Learn (Docentes 2.0 Journal, 2019)
It is a pedagogical proposal that arises from observing that in the trajectories of students of Provincial Oriented Baccalaureate No. 114 programming and computational thinking, fundamental pillars in current national and provincial educational policies, are rarely addressed, and activities that promote the development of skills and competencies necessary for insertion into the society of the future are still at a basic level. A space is then proposed where contents of three curricular spaces of the 2nd year of the Argentine secondary school are integrated: Technology, Mathematics and Geography for the design and creation of educational videogames. It is based on a situational analysis, establishing priorities based on observed situations and acting in the direction of our expectations. The chosen methodology is the ABP.
Keywords: Games; technologies; videogame